Management of tubular oesophageal duplication - A novel approach - Aditi Vijay Dalvi; Maitreyee Save; Paras Kothari; Abhaya Gupta; Shahaji Deshmukh; Apoorva Kulkarni; Saket Jha; Dhvani Shah (Elsevier, 2023)
Background and aim: Oesophageal duplication is a rare congenital malformation which occurs due to embryogenesis errors. It accounts for 15% of all digestive tract duplications, most common being ileal duplications. Here we report a case of tubular Oesophageal duplication and a novel surgical approach for its management.6 year male child, 11 kgs, presented with progressive dysphagia to solids > liquids since birth. He had stunted growth, height and weight were less than 50th percentile. On investigations, Barium swallow and CECT neck with thorax was done to diagnose the pathology and define anatomy. It reported that the child had a congenital partial duplication of the proximal and mid esophagus with midline fold/membrane approximately 6 cm from C5 to D7 level with a dilated lower esophagus and a large hiatal hernia with focal stricture in the right lumen of proximal end. Surgical management was done by excision of oesophageal septum by endoscopic staplers via a gastrotomy under endoscopic guidance per orally and via gastrotomy. Results: Gradually diet started and well tolerated, to be kept on endoscopic surveillance. Conclusions: This is a novel approach to manage oesophageal tubular duplication with minimal risk of mediastinal complications that would occur otherwise by a thoracic approach.